Long-Term Outcomes of Previously Treated Adult and Adolescent Patients with Severe Hemophilia A Receiving Prophylaxis with Extended Half-Life FVIII Treatments: An Economic Analysis from a United Kingdom Perspective - Benson G; Morton T; Thomas H; Lee XY (Dove Medical Press, 2021)
Gary Benson,1 Tim Morton,2 Huw Thomas,3 Xin Ying Lee4 1Northern Ireland Haemophilia Comprehensive Care Centre and Thrombosis Unit, Belfast City Hospital, Belfast, UK; 2DRG, Bicester, UK; 3Biopharm, Novo Nordisk Ltd, Gatwick, UK; 4Biopharm Access, Novo Nordisk A/S, Søborg, DenmarkCorrespondence: Xin Ying LeeNovo Nordisk A/S, Vandtårnsvej 114, Søborg DK-2860, DenmarkTel +45 30777030Email xlee@novonordisk.comBackground: The standard of care for patients with hemophilia A is prophylaxis with factor VIII (FVIII) therapies. Extended half-life (EHL) FVIII products offer a reduced infusion burden compared with standard FVIII treatments. However, comparative evidence between EHLs is lacking.Objective: To develop a pharmacodynamic–pharmacokinetic decision model to predict comparative bleed outcomes of adolescents and adults with hemophilia A receiving treatment with various EHL FVIII therapies, capturing differences in cumulative bleeding episodes, breakthrough bleed resolution and resource costs, as well as quality-adjusted life years (QALYs).Methods: The patient population from the pathfinder 2 Phase III clinical trial was used to understand the link between FVIII levels and annual bleeding rates (ABRs). Pharmacokinetic/pharmacodynamic modeling was subsequently applied to estimate FVIII levels for four EHL FVIII treatments (turoctocog alfa pegol [Esperoct®], rurioctocog alfa pegol [Adynovi®], efmoroctocog alfa [Elocta®], and damoctocog alfa pegol [Jivi®]) to predict comparative ABRs. FVIII consumption costs (due to prophylactic treatment and breakthrough bleed resolution) and resource costs, as well as QALYs, were subsequently estimated from a UK NHS perspective over a 70-year time horizon.Results: Turoctocog alfa pegol prophylaxis resulted in 8– 19% fewer cumulative bleeding episodes versus comparators in the base case scenario. Assuming parity in annual prophylaxis costs, turoctocog alfa pegol prophylaxis reduced the cost of product and resource use to resolve a breakthrough bleed by 9– 25% versus comparators. Prophylaxis with turoctocog alfa pegol was also associated with the most QALYs, representing a discounted QALY gain of 0.35– 1.05 compared with the other treatments.Conclusion: Using a pharmacodynamic–pharmacokinetic decision model, turoctocog alfa pegol prophylaxis was associated with fewer cumulative bleeds, as well as lower product and resource costs related to resolving a breakthrough bleed and most QALYs versus comparators.Keywords: hemophilia A, prophylaxis, factor VIII, FVIII, cost-effectiveness model, turoctocog alfa pegol, Esperoct®